Časovnost in pomenska tipologija samostalnikov - Perko, Gregor (Ars et humanitas, 2012)
The aim of this article is to propose a typology of conceptual noun classes based on the framework of Langacker's Cognitive Grammar. We confine our analysis to nouns expressing temporality. Together with nouns referring to the domain of space, they are grouped into a larger category of extensive nouns. When we speak of temporality, we are referring to predications that are partially or fully characterized relative to the domain of time. Consequently, we distinguish between nouns exhibiting full temporality and nouns exhibiting partial temporality. The former, which represent only a small group of nouns (for instance, moment, period, past, future), profile directly a subpart of the domain of time, in other words, the domain of time is activated as their primary domain. The later profile the succession of states which constitute the central area of the base: this succession, although distributed through conceived time, is profiled in its entirety as a thing and not as a process, and therefore has no temporal profile. This category is further divided into: actions (the region profiled by the predicate is construed as bounded and changing through conceived time: the constitutive states are not all identical), activities (the region profiled by the predicate is construed as unbounded and homogeneous: the constitutive states are all identical) and events (the extension of the profiled region is reduced: it is construed as a point of time). The examples are drawn from Slovene.
Keywords: semantics; semantika; noun; samostalnik; temporality; časovnost